Fundamentals of theoretical concepts of identity phenomenon (The Journal of Psychology and Sociology, 2017)
The article considers the basic approaches to understanding identity. Identity concepts include generalization and systematization of all the qualities of personality combinations, which depend on the biological, psychological, social and cultural factors. Identity analysis uses three methodological principles: primordialism, essentialism and constructivism.Sociologists consider the identity as an interaction between the individual and society. The construction of identity is important for interpersonal and intergroup interactions, and attribution. Satisfying the need to identification with a particular group, explains the individual’s behavior and motives that justified not only their own experiences, but also the interpretation of social interactions. Actions of the individual give meaning to identity, forcing to rethink the past and predict the future of the individual. Identity – an integral part of the internal structure of the person and is a condition for ensuring the sustainability of human. Identity is the feeling of person’s self-identity, his/her relation in the world and to other people. In modern conditions formation of identity comes out not only by means of adaptation and development but also by the conditions of existence, on the basis of interaction of an individual with other people and groups.Self-identity, usefulness, involvement world and other people develop throughout their lives, passes through overcoming crises can vary in a progressive or regressive direction, that is, to be “successful” or “unsuccessful”. Formation of identity in modern conditions is not only a means of adaptation and development, as a condition of existence, the basis for cooperation.
Keywords: identity; adaptation; self-identity; self-consciousness; self-determination; gender.